2021
DOI: 10.1177/0218492320987933
|View full text |Cite
|
Sign up to set email alerts
|

Intratracheal migration of two Kirschner wires after surgery for a clavicle fracture

Abstract: Kirschner wire is frequently used in orthopedic surgery, and migration is not exceptional. Intrathoracic migration is well-known, especially after surgery on the shoulder girdle, however, intratracheal migration is extremely rare. We describe a case of intratracheal migration of two Kirschner wires in a 41-year-old man who had them placed two years previously for a right clavicle fracture. He experienced chest pain followed by hemoptysis. Thoracic computed tomography revealed intratracheal migration. Remove of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…However, the double-arch shape and narrow, irregular medullary cavity of the clavicle have hindered the clinical application of intramedullary fixation devices [ 22 , 23 ]. Furthermore, Harmouchi et al [ 24 ] reported that the Kirschner wires used for fixing intramedullary clavicle fractures were highly prone to displacement; they migrated to critical areas, such as the heart or lungs, causing fatal injuries. To reduce the risks of surgical trauma and postoperative complications, numerous researchers have explored measures to improve this technique [ 12 , 14 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the double-arch shape and narrow, irregular medullary cavity of the clavicle have hindered the clinical application of intramedullary fixation devices [ 22 , 23 ]. Furthermore, Harmouchi et al [ 24 ] reported that the Kirschner wires used for fixing intramedullary clavicle fractures were highly prone to displacement; they migrated to critical areas, such as the heart or lungs, causing fatal injuries. To reduce the risks of surgical trauma and postoperative complications, numerous researchers have explored measures to improve this technique [ 12 , 14 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the double-arch shape and narrow, irregular medullary cavity of the clavicle have hindered the clinical application of intramedullary xation devices [19][20]. Furthermore, Harmouchi et al [21] reported a high risk of fracture displacement with Kirschner wires in intramedullary clavicle fractures, which could migrate to critical areas, such as the heart or lungs and cause fatal injuries. To reduce surgical trauma and postoperative complications, numerous researchers have been exploring measures to improve this technique [12,14].…”
Section: Discussionmentioning
confidence: 99%